Impact of interest rates & capital adequacy on stock returns: profitability's role - Ivansyah, Dimas Fernanda; Widagdo, Bambang; Sa’diyah, Chalimatuz; Fitriasari, Fika (Universitas Muhammadiyah Malang, 2025)
Purpose: This research delves into the factors that determine stock returns within the banking sector listed on the IDX. The primary focus is on assessing the impact of interest rates and capital adequacy ratios, with a consideration of profitability ratios as mediating variables in the resolution Methodology/approach: Quantitative methods were employed for this research, utilizing secondary data derived from the financial reports of each company. Data collection involved the scrutiny of documentation from the annual reports of 14 banks spanning the period from 2018 to 2022, employing a purposive sampling technique. Structural Equation Modeling (SEM) operated through the PLS program was employed for data analysis Findings: The findings indicate that interest rates, capital adequacy ratios, and profitability do not exert any significant influence on stock returns within the banking sector. However, both interest rates and capital adequacy ratios significantly affect profitability. Moreover, profitability does not play a significant mediating role in the relationship between interest rates and capital adequacy ratios concerning stock returns Practical implications: In conclusion, the study suggests that stakeholders should be cautious in overemphasizing traditional financial ratios, and explore broader strategies and variables when analyzing bank stock performance and setting policies Originality/value: This study offers valuable insights into the factors shaping stock returns within the banking sector.